2015
DOI: 10.1007/s13277-014-2190-8
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine impacts differentially on bladder and kidney cancer cells: distinct modulations in the expression patterns of apoptosis-related microRNAs and BCL2 family genes

Abstract: Bladder and renal cancer are two representative cases of tumors that respond differentially to gemcitabine. Previous studies have shown that gemcitabine can trigger apoptosis in various cancer cells. Herein, we sought to investigate the impact of gemcitabine on the expression levels of the BCL2 family members BCL2, BAX, and BCL2L12 and the apoptosis-related microRNAs miR-182, miR-96, miR-145, and miR-16 in the human bladder and kidney cancer cell lines T24 and Caki-1, respectively. Cancer cells' viability as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Gemcitabine plus cisplatin has been researched in advanced urothelial cancer (45); however, no study has explored the efficacy and safety of this regimen in ccRCC. One study showed that the responses of kidney cancer cells to gemcitabine differed (46). By selecting therapeutic regimens based on patient risk score, we can overcome drug resistance and ensure efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine plus cisplatin has been researched in advanced urothelial cancer (45); however, no study has explored the efficacy and safety of this regimen in ccRCC. One study showed that the responses of kidney cancer cells to gemcitabine differed (46). By selecting therapeutic regimens based on patient risk score, we can overcome drug resistance and ensure efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the main function of AKT is the direct inhibition of cell apoptosis (27). The Bcl-2 family is also closely associated with cell apoptosis, numerous members of which, including Bcl-2-associated death promoter (Bad), exert proapoptotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the roles of miRNAs in cancer, inflammation, and immunity [ 3 4 5 ]. Recent studies demonstrated that miRNA profiles can be determined from blood [ 6 7 8 ], including circulating miRNAs and those associated with cancer or damaged tissues [ 9 10 ]. Circulating miRNAs are useful biomarkers for human diseases because they are present in a remarkably stable form in human blood, and the results may have a high degree of reproducibility within individuals [ 1 8 11 12 ].…”
Section: Introductionmentioning
confidence: 99%